LETTERING IN DEAF EDUCATION: CITIZENS OF NOW BUILDING A TOMORROW - de Oliveira Neto, Artur Maciel (2020)
This article aimed to understand what teachers say about their literacy skills. To this end, we discuss the historicity of literacy, about what literacy and literacy would be, seeking to bring current theoretical foundations about the process of acquisition of reading and writing by deaf students enrolled in Early Childhood Education and Elementary School I. We also approach the subject of writing and literacy and the role of the literacy teacher. The research was developed with two teachers and pedagogical support from CAS Mossoró, as they work with specialized educational assistance to deaf students enrolled in the Education modality of the municipal teaching network of Mossoró/RN. The research will be of a qualitative nature, we will use questionnaires and interviews as instruments of data collection, seeking from what approximate answers say about your literacy practice. The study brought as approximations that the teaching and learning process of literacy still occurs in a linear way, when they deal with the meaning of this process in their practice, which is shown as a hybrid understanding, due to the lack of knowledge in the sense of the necessary articulation between students two processes.